Studying the Effect of Perforation Parameters on Vertical Well Performance - Mohammed, Haider Sami; Khazal, Emad Abdullah; Sultan, Hussein Sadeq (Basrah Journal for Engineering Sciences, 2020)
This paper presents a pressure drop analysis in perforated vertical wellbores for different perforation parameters. The effect of the density of the perforations (number of perforation), the phase angle of the perforations, the diameter of the perforation and the flow rate of the crude oil from the perforations on the pressure drop and the productivity index of the perforated vertical wellbores were studied. The analysis of the vertical wellbore was performed numerically using ANSYS FLUENT 15.0 software. Three dimensional, steady-states, turbulent and incompressible fluid flow is assumed during the numerical solution of the governing equations. The results of this study show that, increased perforation density of the perforated vertical wellbore caused an increase in pressure drop, and also, decreased productivity index due to increasing the friction losses. Friction pressure drop has a significant effect on crude oil flow into the wellbore. When the main velocity is 1.5 m/s and the inlet velocity from the perforations is 2 m/s, the friction pressure drop is about 66 % and the acceleration pressure is approximately 34 % of the total pressure drop.